Evaluasi Sistem Pengendalian Internal Siklus Pembelian dan Penjualan pada PT Tirta Saka Pratama Yogyakarta - , LINTANG RESTI P, R.A. Supriyono, Prof., Dr., S.U., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT Tirta Saka Pratama is one of UMKM. PT Tirta Saka Pratama is distributor of beverages which is located on Imogiri Barat Street Km5, Sewon Bantul Yogyakarta. The purpose of this research is to evaluate wheter internal control of purchasing and sales cycles in PT Tirta Saka Pratama is effective or not. For the first step, the researcher prepare a questionnaire about internal control in PT Tirta Saka Pratama. Next, to gain more information the researcher did the observation in PT Tirta Saka Pratama and interview to the person in charge in PT Tirta Saka Pratama. The researcher used COSO as standard to evaluate internal control in PT Tirta Saka Pratama. The researcher compared the theory and the real practice in PT Tirta Saka Pratama. The result of this research show that internal control of purchasing and sales cycles in PT Tirta Saka Pratama is not effective as a tools to reach the objective of company. The internal control system could not protect the companyâs asset so operating activity could not working effectively and efficiently.